Response of e-traders to covid-19 challenges: Empirical evidence from North Macedonia - Nina Angelovska (UTMS Journal of Economics, 2022)
The COVID-19 pandemic caused several short- and mid-term disruptions, to which businesses must adapt. The main goal of this research is to investigate the impact of e-traders response to Covid-19 challenges on online growth. Using existing survey data results linear multiply regression was performed and statistically significant results confirmed that online growth during the Covid-19 emergency was higher in the companies that undertake marketing and delivery adaptation. Further, it was confirmed that e-traders that were selling traditionally and online made higher online growth. Companies with fewer employees were more adaptable to reach higher online growth. Online growth obviously was affected by online sales, and online visits do not statistically significantly influence online growth. The e-traders that believe in the potential for e-commerce in North Macedonia have achieved higher online growth. The timing of the start of the online business does not affect the online growth of e-traders.
Keywords: M20; 330; E-commerce; Marketing adaptation; Delivery adaptation; Pandemic; Online sale